Impact of Gamification on Students' Learning Outcomes and Academic Performance: A Longitudinal Study Comparing Online, Traditional, and Gamified Learning - Georgios Lampropoulos; Antonis Sidiropoulos (MDPI AG, 2024)
This study aims to examine the influence of gamification in students' learning outcomes and academic performance. A longitudinal study was conducted to compare students' academic performance in online learning (2020-2021), traditional learning (2021-2022), and gamified learning (2022-2023). The longitudinal study lasted 3 years and a total of 1001 higher education students were involved. Three research questions were set to be explored and students' viewpoints and experiences were also examined through a questionnaire of 20 questions. This study follows a quantitative research approach. The data refers to students' academic performance, success rate, excellence rate, withdrawal rate, engagement, motivation, and perspectives. In the laboratory part of the course, gamified learning yielded better outcomes over online learning and traditional learning in success rate (39% and 13%), excellence rate (130% and 23%), average grade (24% and 11%), and retention rate (42% and 36%) respectively. In the theoretical part of the course, gamified learning resulted in better outcomes over online learning and traditional learning in success rate (19% and 14%), in excellence rate (125% and 79%), and in average grade (25% and 12%) respectively. In the overall course, gamified learning yielded better outcomes over online learning and traditional learning in success rate (14% and 14%), in excellence rate (122% and 70%), and in average grade (25% and 17%) respectively. The highest increase was observed in students' excellence rate. Students highly regarded gamification as an effective educational approach that can increase their learning outcomes, engagement, productivity, and motivation and trigger both their both intrinsic and extrinsic motivation. The learning experience become more enjoyable and students' basic needs in terms of autonomy, competence and sufficiency, and relatedness and sense of belonging were met. Traditional learning also resulted in better learning outcomes when compared to online learning. Gamification emerged as an effective learning approach which leads to improved learning outcomes and academic performance, learning motivation, engagement, and retention rate over online learning and traditional learning in both theoretical and applied course settings.